Zinc Status and Oral Zinc Tolerance Test in Alcoholic and Non-Alcoholic Cirrhosis - Selim KARAYALÇIN,; Ayten ARCASOY,; Hülya ÇETİNKAYA,; Özden UZUNALİMOĞLU, (Turkish Journal of Gastroenterology, 2020)
-